DEVELOPMENT OF LEARNING ACTIVITIES DURING THE PANDEMIC - Intan Fauzana; Firman; Riska Ahmad (Literasi Nusantara, 2021)
This article will discuss the development of learning activities during the pandemic. There is currently a worldwide pandemic, namely the Covid-19 pandemic which disrupts all community activities, ranging from education, public services, sales, work in offices, hospitals and others. For educational activities, this has very impactful starting from the closed schools which require students to study at home or study online. Compared to before the pandemic, this time will greatly affect learning activities. Therefore, development is needed that can make learning activities during this pandemic period useful and help both students and teachers to carry out learning. The development of this learning starts from building a good learning atmosphere, Keywords – Learning Activities, Learning Atmosphere, Learning Process, Learning Pillars